Chapter 3 Global migration governance, civil society and the paradoxes of sustainability - Likić-Brborić, Branka (Rethinking Globalizations, 2019)
Against the presentation of an asymmetric global governance, this article analyzes the formation of global migration governance with its focus on the politics of migration and development. It traces the marginalization of a rights-based approach to migration and the streamlining of migration governance into business-friendly migration management and a geopolitical securitization agenda. It also reviews the trajectory towards factoring migration into a global development policy discourse as formulated in the UN 2030 Development Agenda. Specifically, it indicates that the inclusion of migration into the Sustainable Development Goals (SDGs) may promote migrant workers' rights because several of these invoke universal human rights instruments, social protection and the observance of the ILO decent work agenda. However, this will only be possible if civil society critically engages powerful state and non-state actors in the process of monitoring the SDGs' implementation, and resists their streamlining into investment and free trade neoliberal development regimes.